Molecular simulation and experimental investigation on enhancement of microbe cement in municipal solid waste incineration fly ash - Sun, Ming; Hu, Kaiyue; Zhang, Yonghong; Wei, Guanqi; Rong, Hui (Frontiers in Materials, 2022)
The enhancing effects of microbe cement on municipal solid waste incineration (MSWI) fly ash have been modeled by molecular dynamics and investigated experimentally. Molecular dynamics is utilized to explore the adsorption mechanism of heavy metal (Pb ions) in cementitious materials in four aspects: intensity distribution, mean square displacement (MSD), radial distribution function (RDF) and time correlation functions (TCF), revealing that the stable formation of chemical adsorption with C-S-H is the main reason. So the leaching of heavy metals can be reduced with cement hydration such as microbe cement with MSWI fly ash. Furthermore, the strengthening effects of microbe cement are inspected experimentally with a compression test, X-ray diffraction, scanning electron microscopy and atomic absorption spectrometer with a content range from 0 to 60%. The results of compressive strength, microstructure inspection and heavy metals’ leaching concentration show that the optimum content of microbe cement for solidifying and enhancing MSWI fly ash is 30% above range.